Nutritional and Gastrointestinal Management of the Patient With Duchenne Muscular Dystrophy - Brumbaugh, David; Watne, Laura; Gottrand, Frederic; Gulyas, Ann; Kaul, Ajay; Larson, Jacqueline; Tomezsko, Jean (Pediatrics (Evanston), 2018)
Advances in treatment and multidisciplinary management have resulted in improved survival of individuals with Duchenne muscular dystrophy (DMD). Updated DMD treatment recommendations as found in the 2018 DMD Care Considerations are aimed to assist multidisciplinary care teams in providing standardized care to their patients, including attention to nutritional and gastrointestinal health. Challenges remain for care teams in accurately estimating height and nutritional status for individuals with DMD. It can be difficult for patients to maintain a healthy weight. Risk factors for obesity include glucocorticoid therapy and loss of ambulation. In contrast, in the later stages of the disease, swallowing dysfunction can lead to poor nutrition and consideration for gastrostomy tube placement. Constipation is highly prevalent, underrecognized, and undertreated in DMD. With this article, we address the assessment and management of gastrointestinal and nutritional issues, as well as clinical controversies.